Long-distance activation of the Myc protooncogene by provirus insertion in Mlvi-1 or Mlvi-4 in rat T-cell lymphomas. - Lazo, P A (1990)
T-cell lymphomas induced by Moloney murine leukemia virus frequently have proviruses integrated at the Mlvi-4 and Mlvi-1 loci, which map approximately 30 and 270 kilobases 3' of the promoter region of the Myc protooncogene, respectively. Provirus insertion in these loci is responsible for the activation of adjacent genes. To determine whether Myc expression was also affected by these provirus insertions, we constructed T-cell hybrids between two rat thymic lymphomas containing a provirus in Mlvi-4 or Mlvi-1 and the murine T-cell lymphoma line BW5147. These hybrids segregated the provirus-containing rearranged alleles from the normal nonrearranged alleles of Mlvi-4 and Mlvi-1, and they carried an intact copy of rat Myc. Using an S1 nuclease protection assay, we observed that the expression of the rat Myc cosegregated with the rearranged Mlvi-4 or Mlvi-1 locus. However, provirus insertion in these loci had no effect on promoter utilization or on the expression of the murine Myc locus. We conclude that provirus insertion exerts a long-range cis effect on the expression of Myc. Therefore, provirus integration in a single locus may affect the expression of multiple genes, some of which may be located a long distance from the site of integration.